Pengaruh Level Penambahan Probiotik dan Ekstrak Buah Balakka (Phyllanthus emblica L.) Terhadap Persentase Karkas dan Bagian-Bagian Karkas Ayam Broiler - Ulina Hutasuhut (Jurnal Ilmu dan Industri Peternakan, 2023)
This research was conducted to determine the effect of supplementation probiotics with different level and balakka fruit extract (Phyllanthus emblica L.) on percentage of carcass weight and carcass parts of broiler chickens. This research materials were used 100 DOC broiler with an average body weight of 44±3,56 g, Lactobacillus plus and Balakka fruit extract. The treatments consistend of basal feed/control treatment (P0); addition of 2% balakka fruit extract (P1); 0,4% probiotics and 2% balakka fruit extract (P2); 0,6% probiotics and 2% balakka fruit extract (P3); 0,8% probiotics and 2% balakka fruit extract (P4). The research method used was a completely randomized design (RAL) with 5 treatments and 4 replications with 5 broiler in each replication. The results showed that supplementation probiotics and balakka fruit extract (Phyllanthus emblica L.) had a significant effect (P<0,05) on percentage of carcass weight and carcass parts. The conclusion of this research was supplementation of probiotics in feed at level of 0,8% and Balakka fruit extract (Phyllanthus emblica L.) in drinking water at level of 2% is the best concentration in increasing the percentage of carcass weight and percentage of breast and thigh weight.